Has International Trade Affected Workers?Bargaining Power? - Ellen Brock; Sabien Dobbelaere (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
In this paper, we investigate whether international trade has affected workers?wages and their bargaining power in particular in the Belgian manufacturing industry over the period 1987-1995 by relying on a rent-sharing framework. Using a sample of more than 12 000 firms, we find that international trade has an effect on workers?wages through changes in the firms?profits. Our regression results reveal that increased foreign competition in the firm of lower export prices reduces both wages per worker and profits per worker. Besides, our findings indicate that technological change is an important detfirminant of the workers?(relative) bargaining power. Globalisation seems also to play some role.
Keywords: C23; D21; F16; F23; J50; L13; 330; Rent Sharing; International Trade; Instrumental Variables; Panel Data; Internationaler Wettbewerb; Lohnniveau; Lohnverhandlungen; Außenhandelspreis; Gewinn; Belgien